Static And Dynamic Mechanical Properties And Strain Rate Sensitivity Of Thermoplastic Based Polymers And Composites Using Split Hopkinson Pressure Bar Apparatus - Omar , Mohd Firdaus (2013)
In this study, an experimental technique, based on the compression Split Hopkinson Pressure Bar (SHPB), was introduced to perform dynamic compression testing whereas a conventional universal testing machine was used to perform static compression testing. These two techniques were used to experimentally investigate the interactive effect of strain rates towards the compressive properties of various thermoplastic-based materials. All of the thermoplastic-based materials used in this study were fabricated using a hot press process. The SHPB results were initially verified and calibrated. The results indicated that all tested thermoplastic specimens (i.e. PP, PE, and PC) showed a great dependency on the strain rate applied; where the yield stress, compression modulus, and compressive strength, were all proportionally increased as the strain rate was increased. Interestingly, both Eyring and basic power law equations were almost agreed with the experimental results over a wide range of strain rates investigated. The effect of molecular structure, on the static and dynamic mechanical properties of thermoplastic polymer, was also determined using polyethylene specimens with different molecular structures (i.e. LDPE, LLDPE, and HDPE). The results indicated that the molecular structure of polyethylene did affect its mechanical properties in terms of yield behaviour, stiffness, strength, rate sensitivity, activation volume, and absorbed energy. For thermoplastic based reinforced composites, two types of particulate fillers were added into the polypropylene matrix namely zinc oxide and mica. It can be clearly seen that the introduction of filler increased the composites’ compressive properties, including their compression modulus, as well as their yield strength. It was also found that the particle content showed an insignificant relationship with strain rate sensitivity and thermal activation volume, for both polypropylene reinforced composite systems. As for the effect of particle-matrix characteristics, silica particles were manipulated to experimentally investigate the correlation between particle size and the mechanical properties of composites under a wide range of strain rates investigated. Interestingly, the size of the silica particles gave significant effects on the compressive properties of the polypropylene-based composites. Quantitatively, composites with nano-sized silica recorded higher compressive properties, in terms of yield strength, ultimate strength and stiffness as compared to composites with micro-sized, for all strain rates investigated.